Green Supply Chain Management Affecting Organization’S Sustainability Performance In Indonesia Wooden Furniture Industry - Juliandina, Martina (2022)
Indonesia is a major producer of hardwood tropical logs and sawn wood, plywood and other boards, paper-making pulp. However, due to reported differently, the amount and value of Indonesia's wood production is difficult to estimate with precision and does not count. There are different threats to the forest in Indonesia, ranging from large-scale logging operations to clearing the scale of family farmers, from clear-cutting to making way for industrial agriculture to frequent fire destruction. The main purpose of this study is to identify the factors such as environmental leadership, green innovation initiative and customer engagement that can affect the organization's sustainability efficiency. The bureaucratic barrier that Indonesia's domestic furniture industry faces is becoming the object of publicity. The study was conducted in Jepara, Indonesia in which 164 registered with the Indonesia Furniture Promotion Council will be the main focus of the target population. The study findings suggested that environmental leadership, green innovation and partnership with customers are important and have a positive relationship to sustainability success. The findings in this study have shown that support from the government is the key to achieving sustainable efficiency.